The relationship between fetal gastroschisis and maternal BMI in a UK population. (16th November 2010) - Derbyshire, A; Taylor, A; Howe, D
Abstract : Gastroschisis is a congenital defect of the abdominal wall through which the intestines protrude. American studies suggest that a low maternal body mass index increases the risk of gastroschisis1 2 but this has not been investigated in a UK population so the authors examined the relationship in women seen in our unit. The authors identified 55 cases of gastroschisis from the Wessex Fetal Medicine Database from 2005 to 2009 and compared these with two control groups from the birth register at the Princess Ann Hospital Southampton. The first group consisted of the next mother in the register to deliver an infant without gastroschisis. The second consisted of the next age-matched mother to deliver an unaffected infant. The authors noted the body mass index (weight in kg/height in m 2 ) at booking for all 165 mothers. Compared with the general population of pregnant women, mothers of affected infants were younger and had lower body mass index (BMI). However, compared with age-matched controls, there was no difference in body mass. Our data do not support the hypothesis that low maternal body mass index is associated with increased risk of gastrochisis in the UK population after controlling for age. At the conference the authors will present the completed data set to examine the effects of maternal BMI and age on the risk of gastroschisis. A low prepregnancy body mass index is a risk factor for an offspring with gastroschisis . Epidemiology 1999 ;10 :717 –721 . The joint effects of maternal prepregnancy body mass index and age on the risk of gastroschisis . Paediatric and perinatal epidemiology 2009 ;23 :51 –57 .